Chemical databases: curation or integration by user-defined equivalence?. (July 2015) - Hersey, Anne; Chambers, Jon; Bellis, Louisa; Patrícia Bento, A.; Gaulton, Anna; Overington, John P.
Graphical abstract: Highlights: A rich variety of data on millions of diverse compounds are now available in public databases that can be used in drug discovery. Differences in database business rules and software limitations mean there will be differences in the structural representation and properties of the same compound in different databases. The size and growth of some databases and the available resources mean manual curation is becoming an increasingly unfeasible task. Resources are available that enable compounds to be matched between databases where they have the same connectivity but other differences in their structures or representations. Abstract : There is a wealth of valuable chemical information in publicly available databases for use by scientists undertaking drug discovery. However finite curation resource, limitations of chemical structure software and differences in individual database applications mean that exact chemical structure equivalence between databases is unlikely to ever be a reality. The ability to identify compound equivalence has been made significantly easier by the use of the International Chemical Identifier (InChI), a non-proprietary line-notation for describing a chemical structure. More importantly, advances in methods to identify compounds that are the same at various levels of similarity, such as those containing the same parent component or having the same connectivity, are now enabling related compounds to be linked between databases where the structure matches are not exact.